Is there Discriminatory Mortgage Pricing against Immigrants in the Spanish Lending Market? - Luis Diaz-Serrano; Josep M. Raya (European Regional Science Association (ERSA), 2011)
In this paper, we investigate whether evidence of discriminatory treatment against immigrants in the Spanish mortgage market exists. More specifically, we test whether, ceteris paribus, immigrant borrowers tend to be charged with higher interest rates on their mortgages than their Spanish born counterparts. To do so, we use a unique dataset on granted mortgages that contains information not only regarding the conditions of the loan but also the socioeconomic characteristics of the mortgagors. We observe that immigrants are systematically charged with higher interest rates. We apply the well known Oaxaca-Blinder decomposition to measure the extent to which this disparate treatment of lenders in mortgage pricing against immigrants is due to discrimination. Our results indicate that approximately two thirds of the gap in the interest rate between Spanish born and immigrant borrowers can be attributed to discriminatory treatment.
Keywords: R21; G21; J14; 330; immigration; discrimination; mortgage pricing; housing market